STRUCTURAL AND DIMENSIONAL ANALYSIS OF THE PISTON AND EXHAUST VALVE OF TOYOTA XLI 1300CC BY USING VARIOUS ALTERNATIVE FUELS - Muhammad Awais; Muhammad Yaseen; Imdad Ali; Ramez Raja; Umair Ahmed Rajput (Spectrum of Engineering Sciences, 2025)
In this study, experimental investigations are conducted on engine components subjected to real- world operating conditions, ensuring the relevance and applicability of the findings. The fuels used in the Toyota XLI 1300cc engine are CNG, LPG, and LNG. Combustion of fuels has various impacts on the piston and exhaust valve, the structural and dimensional characteristics of the Toyota XLI 1300cc engine were characterized. Therefore, employing advanced characterization techniques such as Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), and precise dimensional measurements, the study provides a detailed analysis of the morphological changes, elemental alterations, and dimensional variations induced by the combustion of these alternative fuels. The observations revealed distinctive alterations in the microstructure and elemental composition of the piston and exhaust valve surfaces following exposure to CNG, LPG, and LNG combustion. Furthermore, dimensional measurements unveil potential changes in component geometry, shedding light on the mechanical consequences of adopting these alternative fuels.